Avtobiografija, potopis, avtobiografska potopisna in fiktivna proza Alme Karlin - Borovnik, Silvija (Slavia Centralis, 2020)
The Autobiography, Travelogue, Autobiographical Travelling and Fictional Prose of Alma Karlin The article defines the literary work of Alma Karlin by genre. She was a writer from Celje that wrote in German. Between the two world wars, she was a famous and a very popular author. In Yugoslavia, after the Second World War, she was disregarded and ignored as a “German” author. The article divides her prose into autobiography, travelogue, and fiction. From the standpoint of literary science, Alma Karlin’s prose had been unexplored for a long time. In the article, her examples are analyzed in the European context. Alma Karlin is presented as a double, intercultural, German-Slovenian identity.